Gait Kinematics Analysis of Flatfoot Adults - Marouvo, Joel (2021)
Background: Foot postural alignment has been associated with altered gait pattern. This study aims to investigate gait kinematic differences in flatfoot subjects’ regarding all lower limb segments compared to neutral foot subjects. Methods: A total of 31 participants were recruited (age: 23.26 yo 4.43; height: 1.70 m 0.98; weight: 75.14 kg 14.94). A total of 15 subjects were integrated into the flatfoot group, and the remaining 16 were placed in the neutral foot group. All of the particpants were screened using the Navicular Drop Test and Resting Calcaneal Stance Position test to characterize each group, and results were submitted to gait analysis using a MOCAP system. Results: Significant kinematic differences between groups were found for the ankle joint dorsiflexion, abduction, and internal and external rotation (p < 0.05). Additionally, significant differences were found for the knee flexion, extension, abduction, and external rotation peak values (p < 0.001). Significant differences were also found for the hip flexion, extension, external rotation, pelvis rotation values (p < 0.02). Several amplitude differences were found concerning ankle abduction/adduction, knee flexion/extension and abduction/adduction, hip flexion/extension and rotation, and pelvis rotation (p < 0.01). Conclusion: Flatfooted subjects showed kinematic changes in their gait patterns. The impact on this condition on locomotion biomechanical aspects is clinically essential, and 3D gait biomechanical analysis use could be advantageous in the early detection of health impairments related to foot posture.